2008
DOI: 10.1111/j.1753-4887.2008.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and gastric cancer risk: an update

Abstract: Data from epidemiologic, experimental, and animal studies indicate that diet plays an important role in the etiology of gastric cancer. High intake of fresh fruits and vegetables, lycopene and lycopene-containing food products, and potentially vitamin C and selenium may reduce the risk for gastric cancer. Data also suggest that high intake of nitrosamines, processed meat products, salt and salted foods, and overweight and obesity are associated with increased risk for gastric cancer. However, current data prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 108 publications
(150 reference statements)
2
73
1
5
Order By: Relevance
“…Causes of GC remain not fully understood. Risk factors such as Helicobacter pylori (HP), salted/preserved food consumption, excessive alcohol intake, and tobacco smoking are implicated in the development of GC (Liu et al, 2008;Bertuccio et al, 2009;Gonzalez et al, 2012). Correspondingly, improvements in diet, food storage and a decline in HP infection due to a general improvement in sanitary conditions have been thought to lead to worldwide decline of GC incidence in the last few decades (Thun et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Causes of GC remain not fully understood. Risk factors such as Helicobacter pylori (HP), salted/preserved food consumption, excessive alcohol intake, and tobacco smoking are implicated in the development of GC (Liu et al, 2008;Bertuccio et al, 2009;Gonzalez et al, 2012). Correspondingly, improvements in diet, food storage and a decline in HP infection due to a general improvement in sanitary conditions have been thought to lead to worldwide decline of GC incidence in the last few decades (Thun et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since fruits and vegetables have a high content of AA, it is commonly used as a quality marker. AA is an antioxidant, heat labile and water soluble compound and is able to regenerate tocopherols (vitamin E), from its oxidized form [33]. High temperature, long drying cycle and exposure to oxygen cause a strong reduction of its concentration in fruit and vegetables.…”
Section: Nutritional Quality Changesmentioning
confidence: 99%
“…Selenium supplementation causes the increase in SBP1 expression, which affects cell viability and chemosensitivity of esophageal adenocarcinoma cells (Silvers et al 2010). A large body of evidence has recently demonstrated the protective role of selenium against several major types of cancers including gastric cancer (Liu and Russell 2008;Lee et al 2011). For example, several studies have reported that sodium selenite induces apoptosis in human osteosarcoma, prostate cancer and leukemia (Cao et al 2006;Xiang et al 2009;Chen et al 2012).…”
Section: Introductionmentioning
confidence: 99%